Pengaruh Debt to Equity Ratio, Return on Equity, Net Profit Margin dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Subsektor Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Siti Aisyah Nasution; Apriani Br Pasaribu; Rolista Nainggolan; Emasta Sari Br Karo; Agustinus Buulolo (Universitas Batanghari Jambi, 2022)
The purpose of this research is to prove whether there is an influence between stock prices and DER, ROE, NPM and EPS. The population is 17 companies and 40 samples which are multiplied by five years with this type of quantitative descriptive research, purposive sampling is carried out on the IDX financial statements for 2016-2020. Multiple linear regression analysis is used in testing the data with the researcher testing the classical assumptions first. The coefficient of determination is 0.349, which means that 34.9% of the stock price variable is explained by the DER, ROE, NPM and EPS variables and the remaining 65.1% is explained by other variables not studied. The results of the research show that in the partial test DER, ROE and NPM have no effect, but EPS has an influence on stock prices. And simultaneously DER, ROE, NPM and EPS affect stock prices.